2009
DOI: 10.1002/chem.200901656
|View full text |Cite
|
Sign up to set email alerts
|

Fixing the Chirality and Trapping the Transition State of Helicene with Atomic Metal Glue

Abstract: By combining the intriguing geometrical properties of two classes of well-established molecules, the metallocenes and the helicenes, we propose a hybrid class of structures-the metallohelicenes. In these, the outer most aryl groups of a specific helicene are glued together by a complexing metal atom. This effectively fixes the chirality of the parent helicene, which otherwise easily undergoes thermal racemization. The fixed chirality suggests several interesting applications, ranging from building blocks of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 113 publications
1
21
0
Order By: Relevance
“…As shown in Figure 14, the effect of metal atom deposition on the conductivity of the SWNT thin films diminishes strongly in the sequence Cr > Mo > W, and in order to rationalize this behavior, we briefly review the literature on the structures and energies of the Group 6 hexahapto‐metal arene complexes. The separations between benzenoid rings in the (η 6 ‐C 6 H 6 ) 2 M compounds are as follows: 3.23 Å (M = Cr; electron diffraction),85 3.22 Å (M = Cr; DFT‐TPSS), 3.57 Å (M = Mo; DFT‐TPSS), 3.60 Å (M = W; DFT‐TPSS),102 whereas the thermochemically derived gas phase meta‐ligand bond dissociation enthalpies of the bis‐hexahapto‐benzenoid complexes of the Group 6 metals are given below:103
Thus, based on the benzenoid bond energies in the (η 6 ‐arene) 2 M compounds, it would be expected that the (η 6 ‐SWNT) 2 M complexes would form readily in the case of W and Mo, but of course this has to be balanced against the stability of the initially formed complexes, which are presumably of structure (η 6 ‐SWNT)M (Scheme ), and the propensity of the metal atom to undergo further migration steps. The other issue for Mo and W is the increase in the arene–arene separation that is required for formation of the (η 6 ‐SWNT) 2 M inter‐CNT junction over that which is necessary in the case of chromium, for accommodation of the complexed metal in the van der Waals gap of 3.15 Å within SWNT bundles 84…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 14, the effect of metal atom deposition on the conductivity of the SWNT thin films diminishes strongly in the sequence Cr > Mo > W, and in order to rationalize this behavior, we briefly review the literature on the structures and energies of the Group 6 hexahapto‐metal arene complexes. The separations between benzenoid rings in the (η 6 ‐C 6 H 6 ) 2 M compounds are as follows: 3.23 Å (M = Cr; electron diffraction),85 3.22 Å (M = Cr; DFT‐TPSS), 3.57 Å (M = Mo; DFT‐TPSS), 3.60 Å (M = W; DFT‐TPSS),102 whereas the thermochemically derived gas phase meta‐ligand bond dissociation enthalpies of the bis‐hexahapto‐benzenoid complexes of the Group 6 metals are given below:103
Thus, based on the benzenoid bond energies in the (η 6 ‐arene) 2 M compounds, it would be expected that the (η 6 ‐SWNT) 2 M complexes would form readily in the case of W and Mo, but of course this has to be balanced against the stability of the initially formed complexes, which are presumably of structure (η 6 ‐SWNT)M (Scheme ), and the propensity of the metal atom to undergo further migration steps. The other issue for Mo and W is the increase in the arene–arene separation that is required for formation of the (η 6 ‐SWNT) 2 M inter‐CNT junction over that which is necessary in the case of chromium, for accommodation of the complexed metal in the van der Waals gap of 3.15 Å within SWNT bundles 84…”
Section: Resultsmentioning
confidence: 99%
“…In 1956, Newman and Lednicer [1] synthesized phenantro [3,4-c]phenantrene and introduced the term hexahelicene (later [6]helicene), where the number in brackets indicates the number of rings in the helical backbone.T he interest in these systemsi sd ue to their exceptional structural, chiroptical, and electronic properties. Johanssona nd Patzschke, employing quantum chemical methods, predicted complexes formed by [6]-and [7]helicenes with Cr,M o, W, and Pt and the feasibility of using thesem etals to fix the helicene to as pecific atropisomer. This p-cloud allows the interaction between an helicene and ac ation.…”
Section: Introductionmentioning
confidence: 96%
“…[2][3][4][5] Their distinctive helical structure emergesf rom the sterich indrance of the terminal rings, acquiring chirality even thought hey do not have chiral centers.H owever,s tudies revealed that this deviation from planarity does not represent as ignificant loss in aromaticity, [6] that is, the highly delocalized p-electron surface is preserved and the p-p stacking interactions arise in helicenes with more overlapped layers. [7] Recent studies by Makrlíka nd Vaň ura [8][9][10] have confirmed the existence of the cationic complexes of [6]helicene with Tl + ,A g + ,a nd Li + in the gas phase, which are characterized via electrospray ionization-mass spectrometry.A lso, their computations for the Tl + ,A g + ,a nd Li + complexes indicate that the most probables tructure is ac omplex with the helicene acting as am olecular tweezer andt he cation trapped amid the terminal rings. Johanssona nd Patzschke, employing quantum chemical methods, predicted complexes formed by [6]-and [7]helicenes with Cr,M o, W, and Pt and the feasibility of using thesem etals to fix the helicene to as pecific atropisomer.…”
Section: Introductionmentioning
confidence: 97%
“…This makes them chiral even though they have no center of chirality. The highly delocalized large p-electron system of fully aromatic helicenes along with the previously mentioned inherent chirality predetermines their unique optical [4] and electronic [5] properties, as well as their use in many fields of research including supramolecular chemistry [6][7][8][9][10][11], molecular recognition [12,13], and asymmetric organo-or transition metal catalysis [14,15].…”
Section: Introductionmentioning
confidence: 99%